The Role of Indigenous Institutions in the Implementation of the Malacca Agricultural Revolution Development Program (RPM) in Umatoos Village, West Malacca District, Malacca Regency - Albertus BRIA; Lenny M. TAMUNU; Laurensius P. SAYRANI (International Journal of Environmental, Sustainability, and Social Science, 2023)
The Malaka Agricultural Revolution Program (RPM) has not optimally involved all elements of the Umatoos Village community, while one of the institutions in the village that is capable of mobilizing the community is a traditional institution through the fukun-fukun (tribe head). This research is qualitative with a phenomenological approach. The location of this research was Umatoos Village, West Malaka District, Malacca Regency with 14 informants. The type of research data is qualitative and quantitative, with primary and secondary data sources. Data collection techniques using observation, interviews. Document searches were analyzed using data analysis techniques from Bungin (2012:70). The role of Indigenous Institutions in the implementation of the Malacca Agricultural Revolution Development Program (RPM) in Umatoos Village, West Malaka District, Malacca Regency was analyzed using the opinion of Mintzberg (1973:51) where there are three roles carried out in the organization with the findings that; (a) the interpersonal role of the Umatoos Village customary institution is not utilized for its role as Figurehead, Leader and Liaison Manager, (b) an informational role where the Umatoos Village customary institution is not utilized for its role as monitor, disminator and rapporteur and (c) the Umatoos Village customary institution is not utilized role as a decisional role. The inhibiting factors for the role of traditional institutions in implementing the development of the Malacca Agricultural Revolution (RPM) in Umatoos Village were; (a) the role of village customary institutions as village partners is not utilized, (b) there is no program/activity design and (c) the lack of resources.